(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This study attempts only to forforward an expression and the thought as to why a ‘sports information system inIndiais necessary’. Since no policy can be based on an easy track or quick exercise.This issues forced here need further research, discussion and debate to givesufficient dynamic forced to act upon this idea of progress towards thedevelopment of the ‘national sport information system’ for better achievementsand increased co-operation between countries and sports people on world widebasis.